Housing and quality of life of the elderly: integrative review (Research, Society and Development, 2021)
The aim of this study was to investigate the influence of the housing context on the quality of life of the elderly. It is an integrative review in which the following databases and virtual libraries were selected: PubMED, Web of Science, Scielo, Virtual Health Library (VHL), Scopus, CINAHL and PsycINFO. The identification of 1226 articles, remaining 13 studies after the inclusion criteria. The female gender prevailed, aged over 60 years and resident in Brazil (69.2%, n = 9). The WHOQOL-bref and / or WHOQOL-old questionnaire (61.5%, n = 8) was used to assess the quality of life of the elderly. As for the context of elderly people's housing, the following situations were observed: institutionalized (46.1%, n = 6 articles) alone or with caregivers. The results indicate that the quality of life of the elderly is related to the union of caregivers and adequate infrastructure to meet the peculiar needs of their age, in addition to being fundamental to social participation in maintaining good relationships with their peers.